APLIKASI MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN BAHASA ARAB DI KELAS 1 MADRASAH IBTIDAIYAH ROUDLOTUL HIDAYAH SURABAYA - Ayu Ningsih, Resti Fatma; Sutejo, Sutejo; Puspita, Tuti (YHMM PUBLISHING, 2023)
Language is onee off thee mainn things that must be understood and learned, especially Arabic. With the development of IT today, everything is made easier in learning such as learning using Android. Teaching staff are required to use existing educational standards, so that children are interested and easy to learn. To get data, it is done by meeting directly with the object we are researching so that we get relevant data to support this research. The results showed that the application of android-based Arabic learning media in first grade students of Madrasah Ibtidaiyah Roudlotul Hidayah Surabaya was easy in its application, students could follow the learning well using the application, this android application used the Embarcodero Delphi 10.4 Programming Language. Application modeling is built using the ADDIE method.